64 Linking statewide hospital admission and mortality datasets to investigate events after opioid-related hospitalizations in pennsylvania. (19th September 2017) - Songer, Thomas; Ma, Zhen-qiang; Talbott, Evelyn; Mellers, Michelle; Liu, Stephen; Rager, Judith
Abstract : The burden of opioid misuse relies upon information from one surveillance system. Linked data systems to describe the natural history of opioid misuse are needed to clarify the patterns of risk for opioid users. Methods: The project linked hospital admission and mortality statewide data systems in Pennsylvania from 2000–2014 to identify a cohort of subjects with an index opioid-related hospital admission. Index cases were identified from the first presence of ISW7 ICD-9-CM opioid code in a primary or secondary diagnosis field. The risk for subsequent admission (2000–2014) and mortality (2000–2010) and patterns in readmission and underlying cause of death was assessed. 1 73 849 index cases were identified; of whom 1 03 312 were re-hospitalised, and 17 975 died. Results: 53% of the cohort was identified as having a subsequent hospital admission (for any cause) in the follow-up period. The average time to the next admission was 1.2 years, and the probability of being re-admitted in the first year was 33%. This pattern did not change over time of enrollment in the cohort. About 10% of the cohort from 2000–2010 had died by the end of 2010, with a mean time to death of 11 months following the baseline hospital admission. 800 subjects died at the baseline hospital admission. Drug-related deaths (defined by CDC ICD-10 codes) represented 20% of all causes of death in the cohort. The probability of dying the first year following the index admission was 2% and did not change over time. Death rates varied markedly by age group, with high PMRs for drug-related deaths in the younger age groups (15–44 years). Conclusions: Health care use and mortality is significant and elevated in persons with an initial opioid hospital admission. Significance: Linked surveillance data provide depth to describe the natural history of opioid misuse and the risk for mortality.